1978
DOI: 10.1177/001316447803800448
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Goodenough-Harris Drawing Test and the (Coopersmith) Self-Esteem Inventory

Abstract: Two groups of educable mentally retarded (EMR) primary and secondary pupils were compared on measures of self-esteem and intelligence (IQ) to determine whether scores on a self-drawing test and those on a self-perception test were related. The results of the Pearson product-moment correlations revealed for the secondary EM R subjects a significant relationship between scores on the Goodenough-Harris Drawing Test (DT) and those on the Self-Esteem Inventory (SEI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This can be found in the assessment of self-concept (e.g., Chiu, 1990; Jiranek & Kirby, 1990; Thompson, Lampron, Johnson, & Eckstein, 1990; Tymchuk, 1991) and psychiatric symptoms (e.g., Manikam, Matson, Coe, & Hillman, 1995; Prout & Schaefer, 1985; Reiss & Benson, 1985). Studies should not report psychometric statistics found for the general population because they are unlikely to be applicable to the groups they are studying (e.g., Calhoun, Whitley, & Ansolabehere, 1978; Chassin, Stager, & Young, 1985; Reynolds & Miller, 1985).…”
Section: Psychometric Properties and Target Populationmentioning
confidence: 99%
“…This can be found in the assessment of self-concept (e.g., Chiu, 1990; Jiranek & Kirby, 1990; Thompson, Lampron, Johnson, & Eckstein, 1990; Tymchuk, 1991) and psychiatric symptoms (e.g., Manikam, Matson, Coe, & Hillman, 1995; Prout & Schaefer, 1985; Reiss & Benson, 1985). Studies should not report psychometric statistics found for the general population because they are unlikely to be applicable to the groups they are studying (e.g., Calhoun, Whitley, & Ansolabehere, 1978; Chassin, Stager, & Young, 1985; Reynolds & Miller, 1985).…”
Section: Psychometric Properties and Target Populationmentioning
confidence: 99%
“…The Calhoun et al (1978) study was a correlational one, and the data analysis did not take into consideration the variables of I&, age, or sex. In addition, the instrument used to obtain the self-drawing was the Goodenough-Harris Drawing Test (Harris 1963), which is used primarily to assess intelligence.…”
mentioning
confidence: 99%
“…When their drawings were evaluated for indicators of emotional problems, no statistically significant differences between the two age groups were found. Calhoun and Whitley (1978) did find, however, a statistically significant relationship between a measure of self-esteem (Coopersmith SelfEsteem Inventory, 1967) and the selfdrawings of eight secondary school age students who were considered educable mentally retarded. Ireton, Quast, and Gantcher (1971) also found that the Draw-A-Man Test (DAM) was an effective means of indicating a need for further, more sensitive testing for behavior and learning problems.…”
Section: Studies Ofmentioning
confidence: 85%
“…Calhoun and Whitley (1978) found t h a t the selfdrawings of mentally retarded, secondary school students correlated with a measure of low self-esteem. Ireton, Quast, and Gantcher (1971) found that the Draw-A-Man Test could be used to identify retardation as well as learning problems and could serve as an indicator of the need to further test children ages 4 to 6 in a pediatric clinic.…”
Section: Studies Of the Mentally Retardedmentioning
confidence: 92%